Multi-reservoir enhanced loading of tweezer atom arrays - Xu Yan; Chengdong He; Kai Wen; Zejian Ren; Preston Tsz Fung Wong; Elnur Hajiyev; Gyu-Boong Jo (Physical Review Research)
We introduce a method for improved loading into a single-atom optical tweezer array, utilizing iterative loading with multiple reservoir tweezers. Demonstrated with dual-wavelength tweezer arrays of ^{88}Sr atoms, our approach achieves a 96% loading rate after four reload cycles. This method can significantly enhance existing tweezer rearrangement protocols and reduce optical power consumption for target tweezer arrays, thereby enabling a larger number of atoms in a quantum logic device. Our approach has the potential for implementation with different atomic species and combination with other enhanced loading methods.